Magnetocardiography Using a Magnetoresistive Sensor Array - Adachi, Yoshiaki; Kawabata, Shigenori; Hirao, Kenzo; Okawa, Shuichi; Hasegawa, Yuki; Sekihara, Kensuke; Shirai, Yasuhiro; Shibuya, Tomohiko (International Heart Journal, 2019)
In previous magnetocardiography studies, magnetocardiograms (MCGs) have been obtained using superconducting quantum interference device (SQUID) systems. SQUID is the most sensitive instrument for measuring low-frequency magnetic fields, but it requires liquid helium for cooling, so operating costs are high. In contrast, magnetoresistive (MR) magnetometers function by detecting the change in resistance, caused by an external magnetic field, and have much lower costs. This study was aimed to evaluate feasibility of the MR sensor array for acquiring MCGs.We used an MR sensor array, which was developed for measuring magnetic fields in the picotesla range, with a reduced noise level (TDK Corporation, Tokyo, Japan). A 30-channel MR sensor array was placed in a magnetically shielded room, and the cardiac magnetic field over the anterior chest walls of five healthy subjects was recorded.For all five subjects, MCGs were successfully recorded using the MR sensor array. The cardiac magnetic field corresponding to P, QRS, and T waves on an electrocardiogram (ECG) was detectable by signals averaging 272 ± 27.5 beats.An MR sensor array can be used to measure cardiac magnetic fields. Our results will contribute to the development of low-cost devices for recording MCGs, which will help develop non-invasive diagnostics in cardiovascular medicine.